A method for the quantification of human gastric G cell density in endoscopic biopsy specimens. Issue 5 (May 1981) - McIntyre, R L; Piris, J
Abstract : A previously described method for estimating G cell density in endoscopic biopsy specimens has been modified to take into account observations of the way in which specimens behave when they are deformed and some of the length-measuring characteristics of a grid used to measure the length of tissue profiles. The relationships between particle densities in sections and particle densities in tissue of which the sections are representative are discussed.